Optimal duration of adjuvant endocrine therapy: how to apply the newest data. (November 2017) - Wimmer, Kerstin; Strobl, Stephanie; Bolliger, Michael; Devyatko, Yelena; Korkmaz, Belgin; Exner, Ruth; Fitzal, Florian; Gnant, Michael
Background: The benefit of 5 years of adjuvant endocrine therapy for women with hormone receptor-positive (HR + ) breast cancer (BC) is beyond discussion. Nevertheless, the risk of recurrence of luminal BC persists for 15 years or more after diagnosis. Consequently, approaches of extended adjuvant therapy have been investigated in large clinical trials, with the ultimate aim of further reducing the risk of recurrence in patients with HR + BC. Methods: A review of recently published trial data is presented to provide a solid basis for discussion. A discussion of the side effects of long-term endocrine treatment, multigenetic tests aiming to identify patients at particular risk, and an outlook for further promising targets are additional aims of this review. Conclusion: Extended adjuvant therapy seems beneficial in reducing distant relapse and contralateral BC for a selected group of patients with HR + BC, particularly if aromatase inhibitors (AIs) are used after initial tamoxifen therapy. However, patients with lower risk of recurrence and initial AI therapy may suffer more from side effects than benefit from extended therapy.